Peningkatan Keterampilan Menulis Cerpen dengan Metode Estafet Writing Pada Siswa Kelas IX SMP Negeri 17 Makassar - Mulya, Rachmy Hidayatul; Usman, Usman; Sultan, Sultan (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This study aims to describe the planning, implementation, and assessment of short story writing skills using the relay writing method in class IX students of SMP Negeri 17 Makassar. This research is a type of classroom action research. The subjects of this study were students of class IX.5 of SMP Negeri 17 Makassar. The class totaled 30 students, consisting of 17 boys and 13 girls. The data in this research are process data and outcome data. The data obtained were analyzed using qualitative and quantitative data analysis. . The results showed that there was a huge improvement from cycle I to cycle II. By applying the relay writing learning method, it can increase students' activeness and short story writing skills. Some of the factors behind the improvement of students' short story writing skills are that the relay writing learning method encourages students to be more active in the learning process because the relay writing learning method makes it easier for students to express their ideas.